Zinc ion battery electrolyte with in-situ induced double-layer solid electrolyte interface and application of zinc ion battery electrolyte

By in-situ inducing the formation of a double-layer SEI on the zinc anode surface and using IDA and Zn(OTF)2 additives to form a stable organic-inorganic interface in the zinc battery, the instability problem of the zinc electrode is solved, and high-efficiency zinc battery cycle performance and safety are achieved.

CN121035381APending Publication Date: 2025-11-28ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511184515.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

The interface between zinc metal anode and electrolyte is unstable, including hydrogen evolution reaction, corrosion and uncontrollable dendrite growth. Traditional electrolyte systems are difficult to form a stable SEI, and the in-situ construction of organic-inorganic composite SEI faces competition from reduction potential and insufficient interfacial adsorption regulation.

Method used

Using iminodiacetic acid (IDA) and zinc trifluoromethanesulfonate (Zn(OTF)2) as additives, a double-layer SEI is formed in situ on the zinc anode surface. The outer layer is a hydrophobic organic layer and the inner layer is a rigid inorganic layer. The two layers work together to form a double-layer SEI that can inhibit dissolution and buffer volume changes.

Benefits of technology

It significantly improves the cycle life and safety of zinc batteries, enabling stable operation at high current densities, suppressing dendrite growth and side reactions, and achieving long cycle life and high load deep discharge capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121035381A_ABST
    Figure CN121035381A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc ion battery electrolyte for in-situ induction of a double-layer solid electrolyte interface, the electrolyte comprises a solvent and an additive, the solvent comprises a zinc sulfate solution, and the additive comprises iminodiacetic acid (IDA) and zinc trifluoromethanesulfonate Zn (OTF) 2. The invention also discloses an application of the electrolyte in a zinc ion battery. The zinc ion battery electrolyte provided by the invention can realize in-situ construction of a stable and anti-dissolution dual-function SEI on the surface of a zinc metal negative electrode, so that dendritic crystal growth, side reaction and interface failure are inhibited, the cycle life of a zinc battery is prolonged, and the safety of the zinc battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aqueous zinc-ion battery electrolyte technology, specifically relating to an in-situ induced bilayer solid electrolyte interface zinc-ion battery electrolyte and its application. Background Technology

[0002] Aqueous zinc-ion batteries are considered an ideal choice for next-generation energy storage technology due to their advantages such as low electrolyte cost, environmental friendliness, and high safety. However, the interface between the zinc metal anode and the electrolyte suffers from serious instability issues, including hydrogen evolution reaction (HER), corrosion, and uncontrolled dendrite growth, leading to battery cycle failure or even short circuits. Traditional electrolyte systems (such as zinc sulfate-based electrolytes) struggle to form a stable SEI on the zinc anode surface, mainly due to: 1. Limitations of single additives: Traditional electrolyte additives (such as chloride and fluoride salts) primarily induce the formation of a single-layer inorganic SEI (such as ZnF2 and ZnCO3), which has high solubility in aqueous environments (e.g., ZnF2 has a solubility of 15 mg / mL), leading to continuous dissolution and failure of the interfacial protective layer; 2. Insufficient dynamic compatibility: Inorganic SEIs are highly brittle, exhibiting poor dynamic compatibility at high current densities (>10 mA / cm²). -2 ) or high surface capacity (>5mAh cm⁻¹) -2 ) It is prone to cracking due to volume changes caused by zinc deposition / stripping, which accelerates dendrite penetration; 3. Lack of component synergy: Existing electrolyte systems mostly rely on single additives, which cannot achieve directional composite of organic and inorganic components, making it difficult to balance the mechanical properties and ionic conductivity of SEI.

[0003] In recent years, the design of organic-inorganic composite SEIs has gradually attracted attention. For example, Chinese patent CN119297439A discloses a method for preparing an in-situ organic-inorganic hybrid SEI layer in a zinc-ion battery. The method uses a polysaccharide / polyacrylamide dual-network hydrogel electrolyte as the electrolyte for the zinc-ion battery, and further assembles it with positive and negative electrode sheets to form a zinc-ion battery. During the charge-discharge cycle, an organic-inorganic hybrid SEI layer is generated in-situ at the negative electrode. Furthermore, Chinese Patent CN119381594A discloses an additive for an aqueous zinc-ion battery electrolyte and an electrolyte capable of forming an organic / inorganic hybrid SEI film. The additive contains a pyridine ring, fluorine atoms, and an aldehyde group. The additive adsorbs onto the zinc surface and spontaneously decomposes during charging and discharging, forming a gradient organic / inorganic hybrid SEI film layer together with the electrolyte. The outer SEI film is mainly composed of organic components, while the inner SEI film is mainly composed of inorganic components. This SEI film layer can isolate zinc from direct contact with water, inhibit hydrogen evolution, and promote zinc ion transport. The additive enables the zinc anode to achieve dendrite growth-free operation and side reaction suppression, thereby improving the battery's cycle life.

[0004] However, the in-situ construction of organic-inorganic composite SEI still faces key challenges: 1. Reduction potential competition: The reduction potential of organic additives (such as polymer monomers) is close to that of zinc deposition potential (-0.76V vs. SHE), and the preferential reduction of H2O in the electrolyte hinders its effective decomposition into a film; 2. Insufficient interfacial adsorption regulation: The adsorption mechanism of additive molecules on the zinc surface is unclear, making it difficult to directionally regulate the hierarchical structure and component distribution of the SEI.

[0005] Therefore, developing an electrolyte system capable of in-situ inducing the formation of a stable bilayer SEI is crucial for realizing high-performance zinc batteries. However, few current studies have specifically proposed reasonable design strategies to simultaneously address these issues. Summary of the Invention

[0006] The purpose of this invention is to provide an in-situ induced bilayer solid electrolyte interface for zinc-ion batteries, thereby achieving the in-situ construction of a dual-function SEI that stabilizes the zinc metal anode surface and resists dissolution, thus inhibiting dendrite growth, side reactions and interface failure, and improving the cycle life and safety of zinc batteries.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] A zinc-ion battery electrolyte for in-situ induced bilayer solid electrolyte interface, the electrolyte comprising a solvent and additives, the solvent comprising zinc sulfate solution, and the additives comprising iminodiacetic acid (IDA) and zinc trifluoromethanesulfonate (Zn(OTF)2).

[0009] The technical concept of this invention lies in the fact that IDA and Zn(OTF)2 have strong zinc affinity and can synergistically decompose to induce the formation of a double-layer SEI on the zinc anode surface in situ. IDA preferentially adsorbs onto the electrode surface and decomposes under electrochemical driving into C / N-containing hydrophobic organic compounds (such as [C4H2O]). 14 [N2]SO4) blocks water molecules from contacting the inner layer, relieving interfacial stress; Zn(OTF)2 decomposes to form ZnF2, and CO2 reacts with Zn 2+ The combination forms ZnCO3, providing rigid support and high ionic conductivity. This SEI consists of an outer hydrophobic organic layer (C / N enriched) and an inner rigid inorganic layer (ZnF2 / ZnCO3), which combines the functions of inhibiting dissolution, buffering volume changes, and high-speed ion transport, significantly improving the cycle life and high current resistance of the zinc anode.

[0010] Preferably, the molar concentration of IDA in the electrolyte is 0.02 mol / L to 0.06 mol / L, and the electrolyte exhibits better cycling performance and capacity retention at room temperature.

[0011] Preferably, the molar concentration of Zn(OTF)2 in the electrolyte is 0.2 mol / L.

[0012] Preferably, the molar concentration of IDA in the electrolyte is 0.02 mol / L to 0.04 mol / L. By adjusting the molar concentration of IDA in the electrolyte, the cycling performance and capacity retention of the electrolyte at room temperature can be further improved.

[0013] The present invention also provides an application of the above-mentioned electrolyte in a zinc-ion battery.

[0014] Furthermore, the electrolyte is used in zinc-ion batteries operating under high current.

[0015] The electrolyte is used in applications with current ≥10 mA / cm². -2 In a zinc-ion battery, if the current is 10mA cm -2 -30mAcm -2 .

[0016] Preferably, the zinc-ion battery is a zinc sheet battery, comprising a positive electrode material, a negative electrode material, a separator, and an electrolyte; both the positive and negative electrode materials are zinc sheets, and the separator is a glass fiber separator. Further, the zinc-ion battery is a CR2032 coin cell battery, subjected to charge-discharge cycles in a constant temperature chamber, with an operating temperature of 25°C.

[0017] Preferably, the zinc-ion battery is a zinc sheet / titanium foil battery, comprising a positive electrode material, a negative electrode material, a separator, and an electrolyte; the positive electrode material is titanium foil, the negative electrode material is zinc sheet, and the separator is a glass fiber separator. Further, the zinc-ion battery is a CR2032 coin cell battery, subjected to charge-discharge cycles in a constant temperature chamber, with an operating temperature of 25°C.

[0018] Preferably, the zinc-ion battery is a zinc-sheet||vanadium pentoxide battery, comprising a positive electrode material, a negative electrode material, a current collector, a separator, and an electrolyte; the positive electrode material comprises vanadium pentoxide, Ketjen black, and polyvinylidene fluoride, the negative electrode material is a zinc sheet, the current collector is titanium foil, and the separator is a glass fiber separator. Further, the zinc-ion battery is a CR2032 coin cell battery, the positive electrode material is a slurry of vanadium pentoxide, Ketjen black, and polyvinylidene fluoride in a 7:2:1 ratio, vacuum dried at 60°C for 12 hours, and then cut into 11mm electrode sheets. Preferably, the charge / discharge voltage range of the battery is 0.3–1.6V, and it is subjected to charge / discharge cycles in a constant temperature chamber at an operating temperature of 25°C.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] The zinc-ion battery electrolyte provided by this invention induces the formation of a double-layer SEI (organic-inorganic double-layer solid electrolyte interface SEI) structure on the surface of the zinc metal anode through an in-situ synergistic decomposition strategy. By regulating the adsorption and synergistic decomposition kinetics of the Helmholtz plane (IHP) within the double layer, the electrolyte achieves the in-situ construction of a stable and anti-dissolution dual-function SEI on the surface of the zinc metal anode, effectively inhibiting zinc dendrite growth, side reactions, and SEI dissolution (interface failure), and significantly improving the cycle life and high current density performance (safety) of the battery.

[0021] The zinc-ion battery electrolyte provided by this invention exhibits excellent cycle life in zinc-ion batteries, such as at 10 mA / cm². -2 The cycle life of the double-layer SEI battery exceeds 1690 hours under high current density; under extreme current density (15 mAcm) -2 Under certain conditions, the lifespan is 370 hours; under low current (1 mA cm⁻¹) conditions. -2 The lifespan reached 3750 hours in long-cycle testing;

[0022] The zinc-ion battery electrolyte provided by this invention exhibits excellent high load and deep discharge capabilities when applied in zinc-ion batteries: for example, at 10 mA / cm². -2 Under harsh conditions of high capacity and 89% DOD, the lifespan is 140 hours; the cumulative capacity is 10 mA / cm². -2 8.45 Ah / cm 2 30mAcm -2 10.0 Ah cm -2 ;

[0023] The zinc-ion battery electrolyte provided by this invention exhibits excellent electrochemical stability when used in zinc-ion batteries: for example, at 10 mA / cm². -2 The mean coulombic efficiency (CE) remained at 98.63% for the next 160 cycles at 5 Ag. -1 At high magnification, the capacity retention rate is 61.08% after 5500 cycles. Attached Figure Description

[0024] Figure 1 TEM image of the SEI formed in the zinc-ion battery assembled in Example 1;

[0025] Figure 2 XPS for forming SEI in the zinc-ion battery assembled in Example 1;

[0026] Figure 3 SEM images of zinc deposition morphology in zinc-ion batteries assembled in Example 1, Comparative Example 3, and Comparative Example 4;

[0027] Figure 4The zinc-ion batteries assembled for Examples 1, 2, 3 and Comparative Examples 1, 2, 3 and 4 were tested at 10 mA / cm². -2 Current density and 10mAh cm -2 Cyclic performance data under area capacity;

[0028] Figure 5 The zinc-ion batteries assembled for Example 1, Comparative Examples 3 and 4 were tested at 1 mA / cm². -2 Current density and 1mAhcm -2 Cyclic performance data under area capacity;

[0029] Figure 6 The zinc-ion batteries assembled for Example 1, Comparative Examples 3 and 4 were tested at 15 mA / cm². -2 Current density and 15mAh cm -2 Cyclic performance data under area capacity;

[0030] Figure 7 The zinc-ion batteries assembled for Example 1, Comparative Examples 3 and 4 were tested at 0.5 mA / cm². -2 Current density and 10mAh cm -2 Cyclic performance data under area capacity;

[0031] Figure 8 The zinc-ion batteries assembled for Example 1, Comparative Examples 3 and 4 were tested at 30 mA / cm². -2 Current density and 1mAh cm -2 Cyclic performance data under area capacity;

[0032] Figure 9 The zinc-ion batteries assembled for Example 4 and Comparative Examples 5 and 6 were tested at 10 mA / cm². -2 Current density and 10mAh cm -2 Coulomb efficiency data under area capacity;

[0033] Figure 10 The zinc-ion batteries assembled for Example 5 and Comparative Examples 7 and 8 were tested at 5Ag. -1 Results of long-cycle tests at multiples of [value]. Detailed Implementation

[0034] Example 1

[0035] Take 100 mL of 2M ZnSO4 solution, add 0.532 g IDA and 7.27 g Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm and 0.02 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 button cell is encapsulated with 100 μL of the composite electrolyte, using glass fiber as the separator.

[0036] like Figures 4-8 As shown, the symmetrical cell obtained in this embodiment operates at 10 mA / cm². -2 Current density and 10mAh cm -2 At the area and capacity, the zinc symmetric cell operated stably for over 1690 hours; at 1 mA cm -2 Current density and 1mAh cm -2 At the given area and capacity, the zinc symmetric cell operated stably for over 3750 hours; at 15 mAcm -2 Current density and 15mAh cm -2 At the given areal capacity, the zinc symmetric cell operated stably for over 667 hours; achieving a high depth of discharge (DOD) of 89% (0.5 mA / cm²). -2 10mAhcm -2 It can also cycle continuously for about 140 hours at 30 mAcm. Furthermore, at 30 mAcm... -2 At ultra-high current densities, the cumulative coating capacity (CPC) is 10.0 Ah cm⁻¹. -2 .

[0037] Example 2

[0038] Take 100 mL of 2M ZnSO4 solution, add 0.266 g of IDA and 7.27 g of Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 button cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0039] like Figure 4 As shown, the symmetrical cell obtained in this embodiment operates at 10 mA / cm². -2 Current density and 10mAh cm -2 Under the given area and capacity, the zinc symmetric cell operates stably for approximately 300 hours.

[0040] Example 3

[0041] Take 100 mL of 2M ZnSO4 solution, add 0.798 g of IDA and 7.27 g of Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 coin cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0042] like Figure 4 As shown, the symmetrical cell obtained in this embodiment operates at 10 mA / cm². -2 Current density and 10mAh cm -2 At the given area and capacity, the zinc symmetric cell operates stably for approximately 130 hours.

[0043] Example 4

[0044] Take 100 mL of 2M ZnSO4 solution, add 0.532 g of IDA and 7.27 g of Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. Titanium foil current collector is cleaned with ethanol and dried, and used as the positive electrode. Based on the above electrolyte and electrode materials, a CR2032 coin cell is encapsulated with 100 μL of the composite electrolyte, using glass fiber as the separator.

[0045] like Figure 9 As shown, the half-cell obtained in this embodiment operates at 10 mA / cm². -2 Current density and 10mAh cm -2 Under the given area capacity, the average efficiency of stable cycling for more than 160 cycles is greater than 98.63%.

[0046] Example 5

[0047] Take 100 mL of 2M ZnSO4 solution, add 0.532 g IDA and 7.27 g Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. Titanium foil current collector is cleaned with ethanol and dried, then coated with an electrode active slurry (slurry mass ratio: vanadium pentoxide: Ketjen black: polyvinylidene fluoride = 7:2:1, with N-methylpyrrolidone as solvent). It is placed in a vacuum drying oven and dried at 60 °C for 12 hours, then cut into 11 mm electrode sheets to obtain the positive electrode material. Based on the above electrolyte and electrode material, a CR2032 button cell is encapsulated with 100 μL of the composite electrolyte, using glass fiber as the separator.

[0048] like Figure 10As shown, the full cell obtained in this embodiment is at 5Ag -1 After undergoing 5500 charge-discharge cycles, it still retains 61.08% of its initial capacity.

[0049] Comparative Example 1

[0050] Take 100 mL of 2M ZnSO4 solution, add 1.064 g of IDA and 7.27 g of Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 coin cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0051] like Figure 4 As shown, the symmetrical cell obtained in this comparative example operates at 10 mA / cm². -2 Current density and 10mAh cm -2 At the given area and capacity, the zinc symmetric cell operates stably for approximately 128 hours.

[0052] Comparative Example 2

[0053] Take 100 mL of 2M ZnSO4 solution, add 0.133 g IDA and 7.27 g Zn(OTF)2 sequentially, and stir for 30 min until completely dissolved to obtain a composite electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 coin cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0054] like Figure 4 As shown, the symmetrical cell obtained in this comparative example operates at 10 mA / cm². -2 Current density and 10mAh cm -2 At the given area and capacity, the zinc symmetric cell operates stably for approximately 90 hours.

[0055] Comparative Example 3

[0056] Take 100 mL of 2M ZnSO4 solution, add 7.27 g of Zn(OTF)2, and stir for 30 min until completely dissolved to obtain the control electrolyte. Zinc foil (0.1 mm and 0.02 mm thick) was polished with sandpaper, cleaned with deionized water and ethanol, and used as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 button cell was encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0057] like Figures 4-8 As shown, the symmetrical cell obtained in this comparative example operates at 10 mA / cm².-2 Current density and 10mAh cm -2 At the given area and capacity, the zinc symmetric cell operates stably for approximately 64 hours; at 15 mAcm -2 Current density and 15mAh cm -2 At the area and capacity, the zinc symmetric cell operates stably for only 128 hours; at 1 mAcm -2 Current density and 1mAh cm -2 At the given areal capacity, the zinc symmetric cell operated stably for approximately 1663 hours; achieving a high depth of discharge (DOD) of 89% (0.5 mA cm⁻¹). -2 10mAh cm -2 Under these conditions, it continues to cycle for approximately 100 hours. Furthermore, at 30 mA cm... -2 At ultra-high current densities, the cumulative coating capacity (CPC) is 2.895 Ahcm. -2 .

[0058] Comparative Example 4

[0059] 100 mL of 2M ZnSO4 solution was used as a control electrolyte. Zinc foil (0.1 mm and 0.02 mm thick) was polished with sandpaper and cleaned with deionized water and ethanol, serving as the positive and negative electrodes. Based on the above electrolyte and electrode materials, a CR2032 button cell was encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0060] like Figures 4-8 As shown, the symmetrical cell obtained in this comparative example operates at 10 mA / cm². -2 Current density and 10mAh cm -2 At the given area capacity, the zinc symmetric cell operates for approximately 34 hours; at 15 mA / cm²... -2 Current density and 15mAh cm -2 At the given area and capacity, the zinc symmetric cell operates stably for only 220 hours; 1 mAcm -2 Current density and 1mAh cm -2 At the given areal capacity, the zinc symmetric cell operated stably for less than 278 hours; at a high depth of discharge (DOD) of 89% (0.5 mA cm⁻¹), -2 10mAh cm -2 Under these conditions, it can only cycle for approximately 40 hours. Furthermore, at 30 mAcm... -2 At ultra-high current densities, the cumulative coating capacity (CPC) is 3.255 Ahcm. -2 .

[0061] Comparative Example 5

[0062] Take 100 mL of 2M ZnSO4 solution, add 7.27 g of Zn(OTF)2, and stir for 30 min until completely dissolved to obtain the control electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. Titanium foil current collector is cleaned with ethanol, dried, and cut into 11 mm electrode sheets, serving as the positive electrode. Based on the above electrolyte and electrode materials, a CR2032 button cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0063] like Figure 9 As shown, the half-cell obtained in this comparative example operates at 10 mA / cm². -2 Current density and 10mAh cm -2 With a limited area capacity, it can only cycle about 50 times, resulting in an average efficiency of less than 95%.

[0064] Comparative Example 6

[0065] 100 mL of 2M ZnSO4 solution was used as the control electrolyte. Zinc foil (0.1 mm thick) was polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. Titanium foil current collector was cleaned with ethanol and dried, and used as the positive electrode. Based on the above electrolyte and electrode materials, a CR2032 button cell was encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0066] like Figure 9 As shown, the half-cell obtained in this comparative example operates at 10 mA / cm². -2 Current density and 10mAh cm -2 With its limited area and capacity, it can only cycle stably for less than 20 times.

[0067] Comparative Example 7

[0068] Take 100 mL of 2M ZnSO4 solution, add 7.27 g of Zn(OTF)2, and stir for 30 min until completely dissolved to obtain the control electrolyte. Zinc foil (0.1 mm thick) is polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. Titanium foil current collector is cleaned with ethanol, dried, and coated with electrode active slurry (slurry mass ratio: vanadium pentoxide: Ketjen black: polyvinylidene fluoride = 7:2:1, with N-methylpyrrolidone as solvent). It is placed in a vacuum drying oven and dried at 60°C for 12 hours, then cut into 11 mm electrode sheets to obtain the positive electrode material. Based on the above electrolyte and electrode material, a CR2032 button cell is encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0069] like Figure 10 As shown, the full cell obtained in this embodiment is at 5Ag -1 After 5500 charge-discharge cycles, it retains only 43.45% of its initial capacity.

[0070] Comparative Example 8: 100 mL of 2 M ZnSO4 solution was used as the control electrolyte. Zinc foil (0.1 mm thick) was polished with sandpaper, cleaned with deionized water and ethanol, and used as the negative electrode. The titanium foil current collector was cleaned with ethanol and dried, then coated with an electrode active slurry (slurry mass ratio: vanadium pentoxide: Ketjen black: polyvinylidene fluoride = 7:2:1, with N-methylpyrrolidone as solvent). It was placed in a vacuum drying oven and dried at 60°C for 12 hours to obtain the positive electrode material. Based on the above electrolyte and electrode material, a CR2032 button cell was encapsulated with 100 μL of electrolyte injected into a glass fiber separator.

[0071] like Figure 10 As shown, the full cell obtained in this embodiment is at 5Ag -1 After 5500 charge-discharge cycles, it retains only 28.68% of its initial capacity.

[0072] like Figure 1 As shown, Figure 1 The TEM image of the SEI formed in Example 1 shows that the zinc anode exhibits a clear bi-sided SEI. The interface layer has a uniform amorphous outer layer and a crystalline inner layer with a total thickness of about 17.5 nm. It is also confirmed that the inner crystalline layer contains the lattice patterns corresponding to the inorganic components ZnF2 and ZnCO3. Figure 2 XPS for forming SEI in Example 1, from Figure 2 It can be seen that the organic-inorganic bilayer SEI film formed in situ on the zinc anode surface has the following specific components: the outer layer is a carbon / nitrogen-rich organic layer (containing CC / CH, CN, C=C), which is hydrophobic and amorphous, and the inner layer is an inorganic layer mainly composed of ZnCO3 and ZnF2. Figure 3 SEM images of the zinc deposition morphology in Examples 1, 3, and 4 are shown. Figure 3 The results show that the zinc deposition induced by the double-layer SEI exhibits a dense, uniform, dendrite-free morphology, while the traditional single-layer SEI and SEI-free surfaces form porous dendrites and fractured structures, confirming the key role of the double-layer structure in the uniform deposition and cycle stability of zinc.

[0073] This invention addresses the problems of dendrite growth, hydrogen evolution reaction, and poor mechanical properties of traditional single-layer SEIs in zinc metal anodes. Through the synergistic effect of IDA and Zn(OTF)2 additives, this electrolyte induces the formation of an organic-inorganic bilayer SEI during electrochemical processes: the outer layer is a hydrophobic organic layer (rich in C / N), which inhibits water molecule penetration and buffers volume change stress; the inner layer is a rigid inorganic layer (ZnF2 / ZnCO3), providing high ionic conductivity and mechanical strength. This invention achieves long-term stable cycling and high coulombic efficiency of the battery under high current and high capacity conditions.

Claims

1. A zinc-ion battery electrolyte with an in-situ induced bilayer solid electrolyte interface, characterized in that, The electrolyte includes a solvent and additives, the solvent including a zinc sulfate solution, and the additives including iminodiacetic acid (IDA) and zinc trifluoromethanesulfonate (Zn(OTF)2).

2. The zinc-ion battery electrolyte with in-situ induced bilayer solid electrolyte interface according to claim 1, characterized in that, The molar concentration of IDA in the electrolyte is 0.02 mol / L to 0.06 mol / L.

3. The zinc-ion battery electrolyte with in-situ induced bilayer solid electrolyte interface according to claim 2, characterized in that, The molar concentration of IDA in the electrolyte is 0.02 mol / L to 0.04 mol / L.

4. The application of the electrolyte according to any one of claims 1-3 in a zinc-ion battery.

5. The application according to claim 4, characterized in that, The electrolyte is used when the current is ≥10mA cm -2 Applications in zinc-ion batteries.

6. The application according to claim 4, characterized in that, The zinc-ion battery is a zinc sheet battery, comprising a positive electrode material, a negative electrode material, a separator, and an electrolyte; both the positive and negative electrode materials are zinc sheets, and the separator is a glass fiber separator.

7. The application according to claim 4, characterized in that, The zinc-ion battery is a zinc sheet / titanium foil battery, comprising a positive electrode material, a negative electrode material, a separator, and an electrolyte; the positive electrode material is titanium foil, the negative electrode material is zinc sheet, and the separator is a glass fiber separator.

8. The application according to claim 4, characterized in that, The zinc-ion battery is a zinc sheet / vanadium pentoxide battery, comprising a positive electrode material, a negative electrode material, a current collector, a separator, and an electrolyte; the positive electrode material comprises vanadium pentoxide, Ketjen black, and polyvinylidene fluoride, the negative electrode material is a zinc sheet, the current collector is titanium foil, and the separator is a glass fiber separator.

Citation Information

Patent Citations

  • Preparation method and application for in-situ generation of organic-inorganic hybrid SEI layer in zinc ion battery

    CN119297439A

  • Aqueous zinc ion battery electrolyte additive capable of forming organic / inorganic hybrid SEI membrane and electrolyte

    CN119381594A